The Negotiator - F., Gary Gray.; Jackson, Samuel L.; Kevin Spacey; David Morse; Ron Rifkin; John Spencer; JT Walsh; Siobhan Fallon; Paul Giamatti; Regina Taylor; Bruce Beatty; Michael Cudlitz; et al. (Germany Mandeville Films, 1998)
In the midst of an elaborate conspiracy, an expert negotiator is driven to the edge when he's framed for the murder of his partner, as well as embezzling money from his department's pension fund. His only chance to prove his innocence is to take hostages himself, acquire the services of another expert negotiator, and find out who's running the conspiracy before it's too late.
Samuel L. Jackson is Danny Roman, a hot shot police negotiator and the man of the hour in the police department. One day he wakes up to find that he has been set up, and now the police are after him. In his panic, he takes control of a building. Knowing all the rules of negotiation, Danny asks for the only negotiator he can trust - Chris Sabian (Kevin Spacey). When the police get itchy trigger fingers and want to go into the building shooting, Sabian finds that the only way he can save Danny Roman's life is to go in there and become his partner. Now the police have to deal with both of them.
As a decorated hostage negotiator, Lieutenant Danny Roman has made a career out of talking down dangerous men who don't listen to reason. But he goes off the deep end himself when he is framed for the murder of a colleague investigating corruption in their department. Convinced that the Internal Affairs office contains evidence that can exonerate him, Roman takes everyone inside the building hostage. Roman demands Lieutenant Chris Sabian, known for his anti-violence creed, be brought in to negotiate thinking it will buy him time. When Sabian's attempts for a peaceful resolution are constantly undermined by local authorities, he begins to suspect there may be method to Roman's madness.
Chicago's two top negotiators must face each other. One of them is holding hostages. The other is demanding surrender. And everyone's holding their breath.
Language(s): English
Subtitle(s): English, Turkish, Spanish, Dutch, Swedish, Norwegian, Italian
Keywords: Crime; Drama; Mystery; Thriller